Enhancing the Formation of Porous Potato Starch by Combining α‐Amylase or Glucoamylase Digestion with Acid Hydrolysis. (6th April 2020) - Gonzalez, Ana; Wang, Ya‐Jane
Abstract: Granular porous starch has been prepared from A‐type starch, but not from B‐type starch, due, in part, to the smooth, dense surface of B‐type starch. This study prepares and characterizes acid‐hydrolyzed common corn (A‐type) and potato (B‐type) starches, followed by digestion with α‐amylase or glucoamylase. The results show that, compared to corn starch, potato starch is hydrolyzed faster by acid, whereas the degree of enzyme digestion varies with the starches and enzymes. The acid hydrolyzing conditions destabilize the crystalline lamellae and consequently increase the degree of binding and digestion in both enzymes, which result in the formation of the porous structure in the potato starch. A more defined porous structure is observed in the potato starch after the combination of extended acid hydrolysis and enzyme digestion. B‐type porous starch can be a better colonic delivery system compared to A‐type porous starch due to its more resistance to enzyme digestion. Abstract : The digestion of native potato starch does not form a porous structure because of its unique structure. The destabilization of the structure by acid hydrolysis followed by amylase digestion allows the formation of a porous structure in potato starch. The porous potato starch is capable of better protecting bioactive components through the gastrointestinal system.